Improving Student Learning Achievement through Quantum Teaching in Madrasah - Yusrifaini, Yusrifaini (Universitas Nurul Jadid, 2022)
This study aims to analyze whether the application of quantum teaching learning can improve students' learning achievement of Fiqh at Madrasah Ibtidaiyah Syafiiyah II Banyuanyar, Probolinggo Regency. This study used a qualitative approach to class action research. The stages of action research in a cycle include planning or implementing observation and reflection. Each cycle includes planning (plan), action (action), observation (observation) and reflection (reflection). This cycle continues and will be stopped if it is by the needs and is sufficient. The results showed that quantum teaching learning positively improved student achievement in the class, which was marked by an increase in student mastery in each cycle, namely cycle 1 47.2%, cycle 2 61.1% and cycle 3 86.1%. This research provides implications about the importance of learning design that teachers must carry out so that learning becomes meaningful and of high quality.